1/6m+5/6m-5/6(m+1)=1/6(5m+1)

Simple and best practice solution for 1/6m+5/6m-5/6(m+1)=1/6(5m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1/6m+5/6m-5/6(m+1)=1/6(5m+1) equation:



1/6m+5/6m-5/6(m+1)=1/6(5m+1)
We move all terms to the left:
1/6m+5/6m-5/6(m+1)-(1/6(5m+1))=0
Domain of the equation: 6m!=0
m!=0/6
m!=0
m∈R
Domain of the equation: 6(m+1)!=0
m∈R
Domain of the equation: 6(5m+1))!=0
m∈R
We calculate fractions
We do not support empression: m^3(m

See similar equations:

| 6(b-5)+b2=82 | | 1/2x-10=27 | | 9x2−1=0 | | 2x-4=3x-25 | | 24=-8u+6(u+6) | | 1,128=6(x+19) | | -13=4(5x+-1-11x | | m/6=34 | | -5-12=2y+30 | | 10(w-8)=-160 | | A(p)=p2+9p+20 | | 0=(x^2)-2x-8 | | 6d=9=39 | | 12-8g=-92 | | 157=1+6(5-3v) | | 2x/5=3/11 | | 2x/5=3/1@ | | -7w+3(w-2)=14 | | -2(x+5)-4=22 | | (3x)/(x^2-1)=0 | | 60.50=x5 | | 6p-12=12 | | 5x-5=1+2x | | 17=2b^-6 | | 3b+12=20 | | 6x+6+14x+4=90 | | 30.75=6.15x | | 14x-7x-35=-10x+29 | | -2+2m=-4+6m | | 8/12=6/a | | |x+3|+5x-7x=-9 | | 3y+10=110 |

Equations solver categories